Metateoretiese perspektiewe op liggaamlike probleme as moontlike uitvloeisel van onverwerkte trauma - W. Coetzer; H. Kotzé (Acta Theologica)
This article focuses on the close relationship between unresolved trauma and some physical problems. For most persons, the initial response to trauma is that of denial. However, emotional pain that is suppressed on a continued basis could result in physical problems. With regard to this aspect, attention is also paid to the contribution by research in the field of psychoneuroimmunology. In this regard, special emphasis is placed on the intimate relationship between body and emotions, as well as the role of the immune system. The role of unresolved trauma with regard to some specific diseases is also discussed. In conclusion, a number of specific guidelines regarding a holistic approach in the pastoral counselling of traumatized persons are presented.